The potential impact of the war in Ukraine on the Irish economy - Paul Egan; Adele Bergin; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2023)
The war in Ukraine and the subsequent increase in energy and other commodity prices has dampened the economic outlook. There are increased downside risks to economic activity and there is also considerable uncertainty around any economic projections and how they may evolve in the future. This article uses the ESRI's macro-econometric model COSMO to generate a range of model-based estimates of the potential medium-term impact of the war in Ukraine on the Irish economy. The main shocks to the Irish economy include higher global commodity prices especially for energy and a slowdown in Ireland's main training partners. To capture the impact of the war, the scenario results are compared to a pre-war base. Mild and Severe scenarios are calibrated using commodity price projections from the European Central Bank's December 2022 and March 2023 staff projections. These assumptions regarding energy prices are fed into NIESR's global macroeconomic model, NiGEM, which in turn provides COSMO with projections of key external variables thereby simulating the indirect implications for the Irish economy. The results of our simulations suggest that the domestic economy, as measured by modified domestic demand (MDD), could fall between 1.3 per cent and 3 per cent below the pre-war baseline in the medium term.
Keywords: 330; Kriegsfolgen; Energiepreis; Ölpreis; Gaspreis; Schock; Szenariotechnik; Makroökonometrie; Ukraine; Irland